Implementation of Guided Discovery Learning Model with Videos for Learning on Students’ Science Learning Outcomes in Elementary School Students - Indri, Indri Suci Wardhani; Maryani; Rif’ati Dina Handayani (Jurnal Pendidikan Anak, 2022)
This study examines about the implementation of the Guided Discovery Learning learning model assisted by video learning on science learning outcomes in Elementary School students in Bondowoso Regency. The purpose of this study was to determine whether there was an effect of applying the Guided Discovery Learning learning model assisted by learning videos on science learning outcomes in elementary school students. The research approach used is a quantitative approach with the type of pre-experimental research with a one group pretest and posttest research design. The population and sample in this study were all 6th grade students at SDN Pujer Baru 3, Bondowoso Regency, consisting of 10 students consisting of 6 male students and 4 female students. The data collection technique used was an objective test pretest and posttest of 10 questions in the form of multiple choice adjusted to indicators of cognitive learning outcomes. Based on the results of the study it can be concluded that there is an influence on the application of the Guided Discovery Learning learning model assisted by video learning on science learning outcomes in elementary school students as indicated by the average pretest score of 48.17 and the average posttest of students of 75. The test results the hypothesis shows the sig. 0.000 <0.05, which means H1 is accepted and H0 is rejected. This proves that the Guided Discovery Learning learning model assisted by learning videos has a significant influence on science learning outcomes in elementary school students.